Nonpoint source Pollution in Kansas - Devlin, Daniel L.; Powell, G. Morgan (My University, 1996)
This publication describes how pollution contaminates water in Kansas and how to manage nonpoint source pollution.
MF2204_1996_03
Keywords: MF2204; Environment and Natural Resources; Health and Safety; MF